Promiscuous class II-binding SARS-CoV-2-nuc derived vaccine-peptide induced extensive conventional, innate and unconventional T cell responses - Krickeberg, Naomi; Rammensee, Hans-Georg; Schilbach, Karin (Frontiers in Immunology, 2025)
We describe the T-cell response of two healthy SARS-CoV-2-unexposed volunteers to a SARS-CoV-2 nucleoprotein-derived vaccine peptide predicted to promiscuously bind multiple HLA-DR allotypes. NGS-based bulk TCR-repertoire analysis of peptide-specific T-cell responses 4 (D2) and 27 (D1) weeks after vaccination identified CDR3 regions of TCRα, -β, -γ and -δ chains in T cells responding ex-vivo to the vaccine peptide LLLLDRLNQLESKMS with IFNγ+-secretion. Adaptive repertoires were unique. Donors shared 15 TCRα and 9 TCRβ clonotypes, all public, showing no conserved motifs but TdT-independent “neonatal” CDR3 regions close to the germline. Half the wtSARS-CoV-2 nucleocapsid-reactive adaptive clonotypes show preferential V-segment usage (6/64 Vα and 4-8/45 Vβ chains), and all share/show a N-nucleotide-encoded hydrophobicity in their CDR3 region. VδCα rearrangements (20.4% and 15.3% of the TCRα-repertoires, respectively), Vδ1Cδ γδ-clonotypes homologous to public CD1-restricted Vδ1+ γδTCRs, and the induction of “adaptive” Vδ2Vγ9negative T cells support the role of innate T cells in the immune response.